Early functional outcomes in children with traumatic brain injuries - Rosen, Dalya (My University, 2021)
Traumatic Brain Injury (TBI) is a common cause of disability in children and adolescents. Research in children and adolescents with TBI is still relatively scarce, particularly in low-and middle-income countries. The aim of this study was to determine the early functional outcomes in children with TBI at discharge from acute hospitalisation and at three months’ post discharge. The study included 84 children and adolescents, aged three to twelve, who were admitted to Chris Hani Baragwanath Academic Hospital (CHBAH) with a diagnosis of a TBI, however, the inclusion was not limited to solely children with isolated TBI and in addition included children with associated injuries. The TBI cohort was heterogeneous and included participants with mild (n=71), moderate (n=6) and severe (n=7) head injuries. Motor function was assessed using the Gross Motor Function Classification System (GMFCS); the Gross Motor Function Measure (GMFM-88) and the Movement Assessment Battery for Children–Second Edition (MABC-II). At the three-month follow-up, the primary caregivers completed two questionnaires; The Assistance to Participate Scale (APS) and the Pediatric Quality of Life-Family Impact Module (PedsQL-FIM) to ascertain the amount of assistance the participant requires from the primary caregiver to participate in the home, social and community setting and to determine the impact the TBI has had on the primary caregiver’s health related quality of life (HRQOL) and family function. At hospital discharge, the participants ranged from a level nought to a level four on the GMFCS, indicating that there were participants that required a wheelchair for ambulation. On the GMFM-88 the participants scored the lowest in Dimension E (mean: 87.54%, SD: ±30.12) which consists of running, hopping, and jumping skills. On the MABC-II, the participants scored the lowest in the throwing and catching component (mean: 7.75, SD: ±3.59). The MABC-II revealed that at hospital discharge, 54.76% of participants had no motor difficulties, 23.8% were ‘at risk’ for motor difficulties and 21.43% had a high likelihood of motor difficulties. There was a statistically significant difference between the GMFCS levels (p<0.00), the GMFM-88 (p<0.00), and the MABC-II (p<0.00) scores of the participants at discharge and at the three-month follow-up, with the majority of the sample demonstrating an improvement in motor function. The participants ranged from a level nought to a level two on the GMFCS, indicating an improvement in ambulatory function. The mean total score on the GMFM-88 was 99.38% (SD: ±2.62) indicating almost perfect scores on this outcome measure. The MABC-II revealed that the majority of participants (76.06%) demonstrated no motor disabilities. However, a considerable percentage (23.95%) were still classified as ‘at risk’ of motor impairment or had a high likelihood for motor impairment. There were statistically significant correlations (p<0.00) between the initial GCS score and the functional outcome on the three primary motor outcome measures at the three month follow-up period. There were also statistically significant correlations between the initial GCS score and the type of TBI (p<0.00), and the initial GCS score and the type of associated injuries (p<0.00). There was also a statistically significant correlation (p<0.03) between sex and associated injuries sustained. Although, there was no direct correlation between age and outcome, there was a statistically significant correlation (p<0.01) between the age group and the type of TBI sustained. Younger children were at higher risk of sustaining a TBI, yet the TBI sustained tended to be more mild in nature compared to the older age groups.The majority of the participants were independent in the home, social and community setting at the three-month follow-up (mean APS score: 39.65; range: 19-40; SD: ±2.53). Primary caregivers also reported that the injury had negatively impacted their HRQOL (mean: 69.06; range: 17.92-100; SD: ± 20.44) and family functioning (mean: 64.75; range: 4.17-100; SD: ± 26.78). In conclusion, motor function recovered in 76.06% of the participants of this study. Long term follow-up is warranted to determine residual implications of the injury on a variety of functional domains.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of a Master of Science in Physiotherapy